2015
DOI: 10.1088/0957-4484/26/5/055602
|View full text |Cite
|
Sign up to set email alerts
|

Optically transparent and environmentally durable superhydrophobic coating based on functionalized SiO2nanoparticles

Abstract: Optical surfaces such as mirrors and windows that are exposed to outdoor environmental conditions are susceptible to dust buildup and water condensation. The application of transparent superhydrophobic coatings on optical surfaces can improve outdoor performance via a 'self-cleaning' effect similar to the Lotus effect. The contact angle (CA) of water droplets on a typical hydrophobic flat surface varies from 100° to 120°. Adding roughness or microtexture to a hydrophobic surface leads to an enhancement of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 37 publications
3
23
0
3
Order By: Relevance
“…Once transparency is also introduced into the equation, resistance to durability becomes more problematic since transparent surface texture roughness should not enhance Mie and Rayleigh scattering [18]. Mie scattering occurs when the diameter of the surface features are close to the wavelength of the incident photon, and Rayleigh scattering occurs when the size of the surface features are much smaller than the wavelength of the incident photon.…”
Section: Wetting Theories Surface Roughness and Robust Metastable Sumentioning
confidence: 99%
“…Once transparency is also introduced into the equation, resistance to durability becomes more problematic since transparent surface texture roughness should not enhance Mie and Rayleigh scattering [18]. Mie scattering occurs when the diameter of the surface features are close to the wavelength of the incident photon, and Rayleigh scattering occurs when the size of the surface features are much smaller than the wavelength of the incident photon.…”
Section: Wetting Theories Surface Roughness and Robust Metastable Sumentioning
confidence: 99%
“…These functionalities include self-cleaning [1], anti-icing [2], anti-corrosion [3], and anti-biofouling [4] in addition to the native features of aluminum metal such as lightweight and commendable ductility. A wide variety of fabrication techniques are available for the creation of such coatings, which includes but is not limited to the template method [5], chemical etching [6], electro-spinning [7], chemical vapor deposition [8], self-assembled monolayers [9], and nanocomposites [10][11][12]. The two governing factors for developing a superhydrophobic coating are its surface chemistry (low surface free energy) and surface morphology (nano/microscale roughness) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the superhydrophobic surfaces have been paid much attention, which are developed considerably, for example, self‐cleaning surfaces, anti‐icing surfaces, antibacterial surfaces, antifouling surfaces, or water–oil separation . Superhydrophobic coatings are considered to have more potential future, which have made great progress in recent years . For example, Lu et al reported the feasible preparation of a superhydrophobic coating with the “paint‐spray adhesive” combination structure, which enabled both hard and soft substrates to become superhydrophobic and self‐cleaning.…”
Section: Introductionmentioning
confidence: 99%